(untitled) (Revista Electrónica Calidad en la Educación Superior, 2021)
In this essay, a research guide is developed in the topic of non-technical skills in engineering. Three lines of research with different theoretical and methodological approaches are characterized, namely: the definition of which soft skills should be developed, the identification of gaps between the competences developed by the university with respect to those demanded by the employers and the determination of ways to integrate soft skills in the teaching-learning process. This characterization is based on empirical evidence from studies carried out in the United States, Spain, Germany, Romania, Croatia, India, Lebanon, Malaysia and Indonesia.